Impact of gender on first eye cataract surgery and motor vehicle crash risk for older drivers - Meuleners, Helen; Ng, Jonathon; Fraser, Michelle; Hendrie, Delia; Morlet, Nigel (Wiley-Blackwell Publishing Asia, 2012)
Background: No study to date has examined gender differences in crash risk after cataract surgery. Therefore, this study aimed to determine gender-related differences in the effectiveness of first eye cataract surgery in reducing crash risk for older drivers. Design: This retrospective before and after study used whole population linked data to compare the frequency of police reported crashes 1 year before and 1 year after first eye cataract surgery for the years 1997–2006. Participants: All patients aged 60–85 years who had first eye cataract surgery between 1997 and 2006 in Western Australia and were involved in a motor vehicle crash 12 months before and/ or after surgery. Methods: Two separate generalized estimating equation Poisson models were undertaken for males and females to compare crash frequency before and after surgery. Main Outcome Measures: Police-reported crashes before and after cataract surgery. Results: A large proportion of the cohort involved in a crash either 1 year before or 1 year after first eye cataract surgery were male (n = 1091, 63.6%) compared with female (n = 624, 36.3%). Results from the generalized estimating equation Poisson models showed a significant reduction of 15.3% (P = 0.040) in all police reported crash frequency for males 1 year after cataract surgery. However, there was no significant change in crash frequency after surgery for females. Conclusions: The results of this study suggest that clinicians may need to take gender into account when advising patients on driving safety before and after cataract surgery.